PENGARUH POLA KOMUNIKASI PIMPINAN TERHADAP KINERJA PEGAWAI PERPUSTAKAAN UNIVERSITAS MATARAM - Lubis, Lubis; Silvana, Tine; Siti Khadijah, Ute Lies (Jurnal Kajian Informasi dan Perpustakaan, 2015)
Communication pattern is the pattern of relationship between two or more people in sending and receiving messages in an appropriate manner so that the message is understood. Each leader has a different communication patterns application in moving the organization to achieve the goals of the organization and every leader will establish communication patterns each according to what they understand. This study examines communication patterns leaders formally, informally, processes and forms of communication on the performance of employees in library University of Mataram. The method used in this research is descriptive survey approach and explanatory survey, the data collection techniques used were questionnaires, interviews, observation, and literature study. Population suggestions in this study were employees of the libraries in the University of Mataram as many as 126, then sampling by using Slovin formula with an error tolerance of approximately 0,005 samples in dapatakan so that as many as 90 people and hypothesis testing using path analysis (Path Analysis). These results indicate that the communication patterns leader both formal communication, informal, processes and forms of communication influence on employee performance Mataram University library. So, there are significant positive communication patterns leader in the independent variable formal communication, informal communication, communication processes, and forms of communication, to the dependent variable of employee performance. That is, when a formal communication, informal communication, communication processes, and forms of comm-unication increases, so increasing employee performance. When the formal communication, infor-mal communication, communication process, and the forms of communication decreases, then the em-ployees performance to be decreased as well.Pola komunikasi adalah pola hubungan antara dua orang atau lebih dalam pengiriman dan penerimaan pesan dengan cara yang tepat sehingga pesan yang dimaksud dapat dipahami. Setiap pemimpin memiliki pola komunikasi yang berbeda secara pengaplikasian dalam menggerakan organisasinya untuk mencapai tujuan organisasi dan setiap pemimpin akan membangun pola komunikasinya masing-masing sesuai dengan apa yang mereka pahami. Penelitian ini mengkaji tentang pola komunikasi pemimpin secara formal, informal, proses dan bentuk komunikasi terhadap kinerja pegawai di perpustakaan Univesitas Mataram. Metode penelitian yang digunakan dalam penelitian ini adalah pendekatan survey descriptive dan survey explanatory, dengan teknik pengumpulan data yang digunakan adalah angket, wawancara, observasi, dan studi kepustakaan. Populasi saran pada penelitian ini adalah pegawai perpustakaan yang ada di Universitas Mataram sebanyak 126, kemudian penarikan sampel dengan menggunakan rumus Slovin dengan toleransi kesalahan sekitar 0,005 sehingga sampel yang di dapatakan sebanyak 90 orang dan pengujian hipotesis menggunakan analisis jalur (Path Analysis). Hasil penelitian ini menunjukan bahwa pola komunikasi pemimpin baik komunikasi formal, informal, proses dan bentuk komunikasi berpengaruh terhadap kinerja pegawai perpustakaan Universitas Mataram. Jadi, terdapat pengaruh pola komunikasi pemimpin secara positif variabel bebas komunikasi formal, komunikasi informal, proses komunikasi, dan bentuk komunikasi, terhadap variabel terikat kinerja pegawai. Artinya, bila komunikasi formal, komunikasi informal, proses komunikasi, dan bentuk komunikasi meningkat, maka kinerja pegawai jadi meningkat. Bila komunikasi formal, komunikasi informal, proses komunikasi, dan bentuk komunikasi menurun, maka kinerja pegawai jadi menurun juga.